2019
DOI: 10.1038/s41598-019-46723-6
|View full text |Cite
|
Sign up to set email alerts
|

The MyoRobot technology discloses a premature biomechanical decay of skeletal muscle fiber bundles derived from R349P desminopathy mice

Abstract: Mutations in the Des gene coding for the muscle-specific intermediate filament protein desmin lead to myopathies and cardiomyopathies. We previously generated a R349P desmin knock-in mouse strain as a patient-mimicking model for the corresponding most frequent human desmin mutation R350P. Since nothing is known about the age-dependent changes in the biomechanics of affected muscles, we investigated the passive and active biomechanics of small fiber bundles from young (17–23 wks), adult (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 33 publications
14
17
0
Order By: Relevance
“…Particularly mutation-bearing EDL fibers displayed a myofibrillar Ca 2+ -sensitization already within the aged age group, while in wt littermates, this became only apparent in the senile group. This corroborates well with results from our very recent age-related biomechanical assessment of R349P desmin small fiber bundles, where a very similar desensitization of about 0.2-0.3 pCa units was seen from the adult to the aged age group in EDL bundles, both the het and the hom Haug et al (2019) . For SOL, the single fiber data here do not seem to show a firm consistent trend among the genotypes with age, apart from a large scattering between individual SOL fibers.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Particularly mutation-bearing EDL fibers displayed a myofibrillar Ca 2+ -sensitization already within the aged age group, while in wt littermates, this became only apparent in the senile group. This corroborates well with results from our very recent age-related biomechanical assessment of R349P desmin small fiber bundles, where a very similar desensitization of about 0.2-0.3 pCa units was seen from the adult to the aged age group in EDL bundles, both the het and the hom Haug et al (2019) . For SOL, the single fiber data here do not seem to show a firm consistent trend among the genotypes with age, apart from a large scattering between individual SOL fibers.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our previous assessment in small fiber bundles Clemen et al (2015); Diermeier et al (2017a); Haug et al (2019) , single fibers showed a marked increase in passive restoration forces in RLT experiments, which was at least three-times larger in aged animals with R349P background. Restoration forces were significantly increased and axial compliance accordingly decreased, already in single EDL fibers from aged R349P desmin knock-in animals compared to the equivalent observations found in wt animals in the senile group, only.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations